Proses Administrasi Keuangan Sekolah di Era Society 5.0 - Wiwin Rahma Yanti; Siti Jamila; Ahmad Sabri; Rully Hidayatullah (Pusat Riset dan Inovasi Nasional, 2024)
Administration of funds and equipment is carried out in an effort to improve teaching standards in classrooms. This journal was written using a qualitative approach involving library research, including searching for and evaluating journals or reading materials that are relevant to the journal being discussed. When supervising learning, equipment and financial management must be taken into account. Apart from that, fostering better relations between the educational environment and To realize supervision in the education sector that is based on improving the quality of teaching in schools, community supervision must also be improved. There must be an educational supervision model or plan to expand the research field. In this case, the administration of funds and equipment is carried out as an effort to improve the quality of teaching in schools.